Shared Vulnerability – Collectivity and Empathy in Media Reflections of a Finnish theater Monologue FAT - Hynnä-Granberg Kaisu (Taylor & Francis, 2022)
This article utilizes the concept of “shared vulnerability” to analyze media reflections of a Finnish fat activist monologue FAT. In texts, pictures, and sounds on FAT, gaps between differently-sized women are stitched up and a feeling of an allwomen’s community is offered as a solution to hurtful experiences. I argue that shared vulnerability can signal a welcomed realization of previously hidden privileges on the part of the more normative subject. Yet, talking about shared vulnerability risks ironing out fat women’s experiences by decentering them
or displacing them with those of more-normatively-sized women.